Isolation and selection of Trichoderma spp. strains with high cellulase activity under saline conditions - Trần, Thụy Ái Tâm; Trần, Thị Ngọc Diệu; Trần, Thị Giang; Đỗ, Tấn Khang (Hue University Journal of Science: Natural Science, 2026)
In the context of climate change and saltwater intrusion, research on selecting filamentous fungal strains with salt tolerance and high cellulase activity for agricultural applications has become an urgent issue. The objective of this study was to screen Trichoderma spp. strains exhibiting high cellulase activity and salt tolerance. From rhizospheric soil samples collected around wild rice plants in communes of Dong Thap Province, a total of 110 Trichoderma spp. strains were isolated, showing rich diversity in morphology, color, and characteristic features of the genus. Among them, 29 strains were capable of synthesizing extracellular cellulase enzymes with high CMC (Carboxymethylcellulose) activity, with the diameter of the hydrolysis zones ranging from 25.00 mm to 33.33 mm. The potential strains were further evaluated for salt tolerance at concentrations of 0‰, 5‰, and 10‰ NaCl. As salt concentration increased, the growth, development, and cellulase production of Trichoderma spp. strains decreased. Three potential strains, TP17, TP42, and TP107, were selected for their strong cellulase activity ( ≥ 25 mm); at 10‰ NaCl, the cellulase hydrolysis zone diameters ranged from 25,00 mm to 28,00 mm. The identification results showed that strain TP107 exhibited 98.37% similarity to Trichoderma asperellum (accession number KC993073.1).